COVID-19 pandemic and quarantine-related health disorders in combatants of Ukraine - Danilevska, N. V.; Данілевська, Наталя Володимирівна; Данилевская, Н. В. (Запорізький державний медичний університет, 2021)
Here we expand the existing knowledge about disorders associated with the COVID-19-related pandemic and quarantine. We show that the COVID-19-related pandemic and quarantine can reduce the combat effectiveness of the military, provoking a deterioration in the health of combatants and requires hospitalization. Aim. Investigate the impact of the COVID-19 pandemic and quarantine on the health of Ukrainian combatants. Material and methods. A study was conducted between March 12, 2020 and May 22, 2020 at the Department of Psychiatry, Psychotherapy, General and Medical Psychology, Narcology, and Sexology in Zaporizhzhia State Medical University and Zaporizhzhia military hospital (Ukraine). All combatants who were hospitalized during this period were examined. We analyzed medical records, anamnestic data, and performed psychopathological and psychological examinations of all patients. Results. In 56 % of combatants hospitalized during high quarantine measures, the cause of health disorders is negative COVID-19 pandemic and quarantine-related thoughts that provoke stress. These stressful thoughts associated with the COVID-19 pandemic and quarantine provoke the development of hypertensive emergency (57 % vs 18 %), anxiety syndrome (29 %), dissociative [conversion] disorder (7 %), and exacerbate the negative effects of pre-pandemic diseases, namely, hypertension (43 % vs 27 %), somatoform autonomic dysfunction of the cardiovascular system (29 %), panic disorder [episodic paroxysmal anxiety] (7 %), adjustment disorders (7 %), post-traumatic stress disorder (7 %). Conclusions. Preventive measures need to be developed and applied to combatants to prevent their deteriorating health due to the effects of the COVID-19 pandemic and quarantine stress. У статті розширюємо наявні знання про розлади здоров’я, пов’язані з COVID-19-зумовленими пандемією та карантином. Показано, що пандемія COVID-19 і карантин здатні призводити до зниження боєздатності військовослужбовців, спричиняючи погіршення здоров’я, яке потребує екстреної госпіталізації. Мета роботи – дослідити вплив пандемії COVID-19 та карантину на здоров’я комбатантів України. Матеріали та методи. Дослідження здійснили в період із 12 березня 2020 року до 22 травня 2020 року на кафедрі психіатрії, психотерапії, загальної та медичної психології, наркології та сексології Запорізького державного медичного університету та Запорізького військового госпіталю (Україна). В рамках дослідження обстежили всіх учасників бойових дій, яких госпіталізували в цей період. Здійснили клініко-анамнестичне, психопатологічне та психодіагностичне обстеження контингенту. Результати. У 56 % учасників бойових дій, які госпіталізовані в період найжорсткіших карантинних заходів у країні, в ґенезі причин порушень здоров’я лежали стресогенні переживання, асоційовані з пандемією COVID-19 і карантином. Ці стресогенні переживання – чинники розвитку гіпертонічного кризу (57 % vs 18 %), тривожного синдрому (29 %), дисоціативного [конверсійного] розладу (7 %), екзацербували прояви передпандемічних захворювань: гіпертонічної хвороби (43 % vs 27 %), соматоформної вегетативної дисфункції серцево-судинної системи (29 %), панічного розладу [епізодичної пароксизмальної тривоги] (7 %), розладу адаптації (7 %), післятравматичного стресового розладу (7 %). Висновки. Виявили зв’язок між пандемією COVID-19, карантином і погіршенням здоров’я військовослужбовців. Це вказує на необхідність розроблення та впровадження профілактичних заходів для учасників бойових дій, аби запобігти погіршенню їхнього здоров’я під впливом стресогенних переживань, що пов’язані з COVID-19-зумовленими пандемією та карантином. В статье расширяем имеющиеся знания о расстройствах здоровья, связанных с COVID-19-обусловленными пандемией и карантином. Показано, что пандемия COVID-19 и карантин способны приводить к снижению боеспособности военнослужащих, провоцируя ухудшение здоровья, требующее экстренной госпитализации. Цель работы – исследовать влияние пандемии COVID-19 и карантина на здоровье комбатантов Украины. Материалы и методы. Исследование проводили в период с 12 марта 2020 года по 22 мая 2020 года на кафедре психиатрии, психотерапии, общей и медицинской психологии, наркологии и сексологии Запорожского государственного медицинского университета и Запорожского военного госпиталя (Украина). В рамках работы обследовали всех участников боевых действий, госпитализированных в этот период. Осуществили клинико-анамнестическое, психопатологическое и психодиагностическое обследования контингента. Результаты. В 56 % случаев у участников боевых действий, госпитализированных в период жёстких карантинных мероприятий в Украине, в генезисе причин нарушений здоровья лежали стрессогенные переживания, ассоциированные с пандемией COVID-19 и карантином. Эти стрессогенные переживания – факторы развития гипертонического криза (57 % vs 18 %), тревожного синдрома (29 %), диссоциативного [конверсионного] расстройства (7 %), экзацербировали проявления предпандемических заболеваний: гипертонической болезни (43 % vs 27 %), соматоформной вегетативной дисфункции сердечно-сосудистой системы (29 %), панического расстройства [эпизодической пароксизмальной тревоги] (7 %), расстройства адаптации (7 %), посттравматического стрессового расстройства (7 %). Выводы. Установленная связь между пандемией COVID-19, карантином и ухудшением здоровья военнослужащих указывает на необходимость разработки и применения профилактических мер к участникам боевых действий для предотвращения ухудшения их здоровья под влиянием стрессогенных переживаний, спровоцированных COVID-19-обусловленными пандемией и карантином.
Розлади здоров’я, пов’язані з пандемією COVID-19 і карантином, у військовослужбовців України
Нарушения здоровья, связанные с пандемией COVID-19 и карантином, у военнослужащих Украины
ORCID ID: 0000-0002-7854-9007
Keywords: COVID-19; pandemic; quarantine; health disorders; military personnel; пандемія; карантин; розлади здоров’я; учасники бойових дій; пандемия; расстройства здоровья; участники боевых действий